IDENTIFICATION OF SECONDARY METABOLITES CLASSES IN LEAF ETHANOLIC EXTRACTS OF Byrsonima verbascifolia, Cardiopetalum calophyllum, Curatella americana AND Qualea grandiflora (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The Cerrado represents a phytochemical bank of great importance for humanity. The objective of this study was to identify, through phytochemical prospecting, the main chemical compounds present in the leaf extracts of B. verbascifolia, C. calophyllum, C. americana and Q. grandiflora. In this study, leaves of the species were collected in a permanent preservation area (APP) in the city of Rio Verde, State of Goiás. Ethanolic foliar extracts for the presence or absence of the main phytocomponents: organic acids, reducing sugars, alkaloids, anthraquinones, catechins, coumarins, depsidones, olefinic bonds, phenols, flavonoids, cardiotonic glycosides, polysaccharides, purines, saponins and tannins were evaluated. Except for olefin, polysaccharide and purine groups, positive results were observed for most of the secondary metabolic classes. Preliminary research on the ethanolic foliar extracts of these four species makes possible a preliminary evaluation about their phytochemical characteristics and should be evaluated for their contents and major compounds so that they can be used as herbal medicines or industrial synthesis.